Penerapan blended learning melalui inisiasi pembelajaran online menggunakan website dan Google Hangout dengan melibatkan praktisi industri sebagai upaya peningkatan kualitas pembelajaran di kelas business environment - Tuti Purwaningsih (Refleksi Pembelajaran Inovatif, 2020)
Current technological developments require the world of education to continue to improve the paradigm change in learning methods in the classroom. The rapidity of this technology makes it easier for everyone to access information. This is quite beneficial to the world of education for both students and lecturers. The ease of finding material and sources of information that are sufficiently up-to-date makes this technological development open our horizons. One of the subjects that is quite affected by the development of technology is the business environment. Students are required to be able to have a start-up spirit, be able to design business processes in the world of technology, be able to make start-ups with their classmates, solve social problems around them with technology that brings benefits. The rapid change from this technology makes new start-up start-ups emerge with various types, adjusting the needs of today's society and always undergoing changes in an effort to continue to survive in the market. This requires that learning in class is not only face to face with lecturers, but students are also required to play an active critical role in the problems that arise in the community and they are able to find technological solutions to help solve these problems. This can be done quite well if students are given an inspirational stimulus from industry start-up experts. Students are also required to be able to display their start-up products and be exhibited to industry practitioners to evaluate whether they are good enough or not. Therefore the implementation of this teaching grant aims to improve the quality of learning in the classroom by applying Lesson Study for Learning Community (LSLC) with the Blended Learning method through the initiation of online learning using the website & google hangout by involving industry practitioners as an effort to improve the quality of learning in the business environment class. The results of the implementation of this grant included the formation of 29 new mini start-ups in accordance with the interest of the study group, the class website with the address url www.thebusinessenvironment.com and an increase in the insight of students in today's industrial development, especially start-up. In implementing this teaching grant program, some limitations were faced between the classrooms that were less comfortable for lecturer mobility and the activities of the student study group, the number of students in the class was still too much with a class size that was not too wide. The suggestion for further development is to add a virtual class meeting session with the industry because it is very useful to update the latest start-up information every time, which certainly changes. The practical implication that is felt is the formation of a study group of students who have their respective visions regarding the mini-start-up specialization they want to work on.